Anxiety and Depression in Parkinson’s Disease - S. E. Starkstein; R. G. Robinson; R. Leiguarda; T. J. Preziosi (Behavioural Neurology)
We examined a consecutive series of 40 patients with Parkinson's disease (PD) for the presence of anxiety. We found that 40 % met DSM-III criteria for generalized anxiety disorders, and half of them also met criteria for either major depression or minor depression. While depression was associated with long duration of illness and more severe cognitive and physical impairments, anxiety was not associated with greater impairment. We conclude that anxiety, with or without depression, constitutes a frequent psychiatric problem among patients with PD.